Incorporation of [(15)N]Ammonia by the Cellulolytic Ruminal Bacteria Fibrobacter succinogenes BL2, Ruminococcus albus SY3, and Ruminococcus flavefaciens 17 - Atasoglu, Cengiz (American Society for Microbiology, 2001)
The origin of cell nitrogen and amino acid nitrogen during growth of ruminal cellulolytic bacteria in different growth media was investigated by using (15)NH(3). At high concentrations of peptides (Trypticase, 10 g/liter) and amino acids (15.5 g/liter), significant amounts of cell nitrogen of Fibrobacter succinogenes BL2 (51%), Ruminococcus flavefaciens 17 (43%), and Ruminococcus albus SY3 (46%) were derived from non-NH(3)-N. With peptides at 1 g/liter, a mean of 80% of cell nitrogen was from NH(3). More cell nitrogen was formed from NH(3) during growth on cellobiose compared with growth on cellulose in all media. Phenylalanine was essential for F. succinogenes, and its (15)N enrichment declined more than that of other amino acids in all species when amino acids were added to the medium.